ANALISIS ATAS PENGHITUNGAN PENGHASILAN KENA PAJAK SEBAGAI DASAR PENENTUAN BESARNYA PAJAK PENGHASILAN TERUTANG YANG DILAKUKAN “OPQ” - Sobo Sitorus; Haekal Pratama (Jurnal Pajak dan Bisnis, 2020)
This study aims to determine whether the calculation of taxable income as a basis for determining the amount of income tax payable of a company is in accordance with the provisions of the tax laws. What problems or titles are faced by companies as taxpayers in calculating taxable income. What efforts did the company make in overcoming these obstacles? By using descriptive-analytical research methods and interviews with relevant sources and literature studies, the results show that the calculation of taxable income made by the company is not fully in accordance with the provisions of tax regulations. Constraints faced are errors in interpreting the costs that can be charged as a deduction from gross income in order to obtain the amount of taxable income.